Estimation of Sales Potential for ILOMEDIN in Prevention of Contrast – Induced Nephropathy (CIN): A Business Case - Wetzel, Carolin (2010)
This report is based on an internship undertaken at Bayer Healthcare, Berlin. The scope of the internship and report was to analyze the feasibility and financial viability of expanding an existing brand in the Bayer portfolio called Ilomedin into a different and unrelated medical indication. Data collection for the business case was primarily facilitated by interviewing Key Opinion Leaders from the medical fraternity and from internal Bayer resources as well as from published literature on the concerned topic. Literature review pertaining to the project was carried out largely on the topics of lifecycle management, new product development and forecasting. This report begins by analyzing Ilomedin´s current stage in its lifecycle. It then analyses the current debate and discusses the merits of Ilomedin as a preventive medication for contrast-induced nephropathy (CIN). By reviewing certain theories, constructs and models of new product development, this report discusses the merits and demerits for the expansion of the use of Ilomedin as a preventive care for a new indication, i.e. CIN, at the current stage in its lifecycle. For the financial analysis we use certain forecasting tools to project the profit & loss and discounted cash flows to gauge the viability of the project. Finally, this project brings to light the need for having a dedicated development process for expansion of in-market drugs into new indications, especially in a capital intensive industry like pharmaceuticals.